The Niemann–Pick C1-like 1 rs2073547 polymorphism is associated with type 2 diabetes mellitus in a Chinese population. Issue 9 (September 2019) - Huang, Zhenxing; Tan, Ruyin; Meng, Liheng; Yang, Haiyan; Liang, Xinghuan; Qin, Yingfen; Luo, Zuojie
Objective: To explore the association between Niemann–Pick C1-like 1 gene ( NPC1L1 ) single nucleotide polymorphisms and type 2 diabetes mellitus (T2DM) in a Chinese population. Methods: Using propensity score matching, 490 T2DM patients and 490 matched controls were recruited from 13 communities in Guangxi, China. NPC1L1 rs217386 and rs2073547 genotyping was performed using a MassARRAY system. Results: The rs2073547 genotype distribution differed significantly among patient groups. Low-density lipoprotein cholesterol levels were similar among different rs2073547 genotypes and alleles. The rs2073547 AG genotype was significantly more prevalent in patients with T2DM. After adjusting for risk or protective factors for diabetes, AG and GG+AG genotypes of rs2073547 were associated with significantly increased risks of T2DM. Compared with the AA genotype, the AG genotype was associated with a significantly higher risk of T2DM in participants with gamma-glutamyl transpeptidase (GGT) <45 U/L, systolic blood pressure (SBP) ≥140 mmHg, or triglyceride <1.70 mmol/L. In participants with GGT <45 U/L or SBP ≥140 mmHg, the GG+AG genotype was associated with a significantly higher T2DM risk versus the AA genotype. Conclusions: The rs2073547 polymorphism of NPC1L1 may be related to T2DM susceptibility in the Chinese population.